2011
DOI: 10.1002/etc.557
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of metals to roots of cowpea in relation to their binding strength

Abstract: Metal phytotoxicity is important in both environmental and agricultural systems. A solution culture study examined the toxicity of 26 metals to roots of cowpea (Vigna unguiculata (L.) Walp.); new data were collected for 15 metals and published data for 11 metals. Metal toxicity, calculated as causing a 50% reduction in root elongation rate, was determined based on either the measured concentration in the bulk solution (EC50(b)) or the calculated activity at the outer surface of the plasma membrane (EA50(0)°). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
(63 reference statements)
4
26
1
Order By: Relevance
“…Based on the median effective activity, EA50 M , substantial differences were found between the sensitivities of cowpea, Vigna unguiculata, reported by Kopittke et al [17] and of lettuce, L. sativa, found in the present study (Table 1). On the basis of the estimations of EA50 M , L. sativa had higher tolerance to Zn 2þ and Ag þ but was more sensitive to Cu 2þ than V. unguiculata.…”
Section: Resultscontrasting
confidence: 43%
“…Based on the median effective activity, EA50 M , substantial differences were found between the sensitivities of cowpea, Vigna unguiculata, reported by Kopittke et al [17] and of lettuce, L. sativa, found in the present study (Table 1). On the basis of the estimations of EA50 M , L. sativa had higher tolerance to Zn 2þ and Ag þ but was more sensitive to Cu 2þ than V. unguiculata.…”
Section: Resultscontrasting
confidence: 43%
“…Error bars are shown, although they are often smaller than the symbols. Data from Kopittke et al , Blamey et al , and Kopittke et al . ( C ) Relationship between HLScale values and concentrations of 8 cations in the bulk solution that have been found to induce toxic effects in solution culture.…”
Section: Relationships Between Cation Physicochemical Properties and mentioning
confidence: 99%
“… The EC50 is the concentration (µM) of cations in the bulk solution reducing root elongation by 50%, taken from Kopittke et al for roots of cowpea.…”
Section: Relationships Between Cation Physicochemical Properties and mentioning
confidence: 99%
“…Cation exchange and complex formation with functional groups on plant roots were main mechanisms for biosorption of heavy metals by plant root materials1617. There were extensive investigations on the adsorption of heavy metals by cell walls and cell plasma membranes of plant roots as related to rhizotoxicity and uptake of heavy metals by plant roots19202122232425. It was found that electric potential induced by surface charge on plasma membranes was one of main factors determining ion activities of heavy metals on plasma membranes and their toxicity to plants20212223.…”
mentioning
confidence: 99%
“…There were extensive investigations on the adsorption of heavy metals by cell walls and cell plasma membranes of plant roots as related to rhizotoxicity and uptake of heavy metals by plant roots19202122232425. It was found that electric potential induced by surface charge on plasma membranes was one of main factors determining ion activities of heavy metals on plasma membranes and their toxicity to plants20212223. However, the investigations on the adsorption of heavy metals by entire plant roots as related to their toxicity and uptake to and by plants were rarely found in literature2627.…”
mentioning
confidence: 99%